2016
DOI: 10.5713/ajas.16.0553
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary onion (Allium cepa) extract supplementation on performance, apparent total tract retention of nutrients, blood profile and meat quality of broiler chicks

Abstract: ObjectiveThis study was conducted to investigate the effect of dietary onion (Allium cepa) extract (OE) supplementation on growth performance, apparent total tract retention (ATTR), blood profile, carcass characteristics and meat quality in broilers.MethodsFour hundred male broiler chicks (Ross 308, 3-d old) were randomly allocated to four dietary treatments for 28 d feeding trial. Each treatment has five replications with 20 birds each. Four dietary treatments were designated according to the OE supplementati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 24 publications
5
19
0
Order By: Relevance
“…Moreover, onions contain non-digestible prebiotic and fructooligosaccharide (FOS) components, which are fermented by bifidobacteria to further maintain intestinal and colon health (63). Another reason for the improved AID ratio of amino acids (26) and increased feed consumption (17, 64) could be the increased retention of the total pathway of energy and ether extract. The increased feed consumption is due to the favorable taste and flavor of onion extract (65).…”
Section: Growth Performance and Digestibilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, onions contain non-digestible prebiotic and fructooligosaccharide (FOS) components, which are fermented by bifidobacteria to further maintain intestinal and colon health (63). Another reason for the improved AID ratio of amino acids (26) and increased feed consumption (17, 64) could be the increased retention of the total pathway of energy and ether extract. The increased feed consumption is due to the favorable taste and flavor of onion extract (65).…”
Section: Growth Performance and Digestibilitymentioning
confidence: 99%
“…Aditya et al (26) demonstrated that BWG is generally higher in broiler chickens fed with 7.5 g/kg of onion extract, and the feed intake was increased by supplementing 5, 7.5, and 10 g of onion FIGURE 2 | A representative photomicrograph of 40× magnification H&E stained small intestine sections of the broiler chickens. The sections from the duodenal segments from PROE0group showed separate tall and arranged intestinal villi with (arrow) free lumen (A), the duodenal segments from PROE1 group showed apparently separated tall and arranged intestinal villi with free lumen (B), the duodenal segments from PROE2 group revealed marked active intestinal villi and crypts which characterized by limited goblet cells metaplasia (star)' increased sizes and rows of enterocytes (thick arrow) with arranged lamina propria beside some desquamated villi (small arrow) (C).…”
Section: Growth Performance and Digestibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The inclusion of alliums in poultry diets has also been reported to improve color stability, fatty acid composition [63], sensory properties [14,111], and the anti-oxidative ability of meat [64,66,79]. Choi et al [63] reported the color stability of meat (highest redness and yellowness) by the incremental levels of garlic powder (1-5%) dietary supplementation and the effect was ascribed to the reduced metmyoglobin formation and oxidation in thigh muscle of chicks.…”
Section: Effects On Product Qualitymentioning
confidence: 99%
“…However, Abdullah et al [122] reported no effects of garlic supplementation on the meat quality such as cooking loss percentage, shear force, color coordinates). The improved anti-oxidative capability of chicken meat by the dietary allium supplementation was attributed to the accumulation of antioxidant compounds such as flavonoids and OSCs [66,79]. Indeed, the utilization of dietary alliums to improve the quality of poultry products should be done carefully because high doses of the allium may reduce overall acceptability with altered taste and odor.…”
Section: Effects On Product Qualitymentioning
confidence: 99%